BUSINESS ANALYSIS MODEL USING CANVAS BUSINESS MODEL APPROACH TO KJPP YANUAR BEY AND PARTNERS - Ruspriono (Dinasti Publisher, 2020)
This study aims to determine the business model with Business Model Canvas on KJPP Yanuar Bey and Partners (Y&R) engaged in the Appraisal and Consultant. The objectives of this study are: (1) Identifying the business model at Y&R using BMC, (2) Creating a business model improvement on Y&R. The Business Model will be reviewed on every BMC element consisting of customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structures with SWOT Analysis. The research method used is descriptive qualitative analysis. Data collection was carried out using interviews and observation techniques. This research is focused on creating a new business model with a BMC approach that looks at Y&R through the nine elements of BMC. The results of this study indicate that the business model that has been carried out by Y&R found weaknesses in the nine elements of BMC, therefore it is necessary to improve all elements.